'Making it Meaningful': Co-designing an intervention to improve medication safety for people from culturally and linguistically diverse backgrounds accessing cancer services. - Ashfaq Chauhan; Bronwyn Newman; Elsa Roberto; Ramesh Walpola; Holly Seale; Melvin Chin; Reema Harrison (The Beryl Institute, 2023)
This study reports on the process of using an adapted Experienced-Based Co-Design (EBCD) conducted with culturally and linguistically diverse (CALD) consumers and cancer service staff to co-design the novel 'Making it Meaningful'(MiM) instrument at a cancer service in Australia. Multi-source experiential and contextual information was gathered in phase 1 of the co-design and this evidence, coupled with knowledge gathered via a feedback event was used to inform three co-design workshops in phase 2. A series of meetings were conducted prior to and in between the workshops. Theory was progressively integrated into the workshop content. Two Mandarin speaking CALD consumers and three cancer service staff participated as co-design members. Workshops were supported by a multilingual fieldworker, co-facilitated by researchers and a consumer co-facilitator, and conducted using a hybrid model (face-to-face or online participation). In the first workshop members democratically selected to focus on a strategy to enable CALD consumers to make non-emergency urgent contact with the cancer service for medication related communication. The second workshop resulted in consensus to develop an accessible instrument that would identify appropriate contacts and information sources for medication management between appointments. In the third workshop, the prototype MiM instrument was developed and refined. The MiM is a novel instrument designed with CALD consumers to enhance their knowledge of medication management and empower them to contact cancer service staff about medication safety concerns. Feasibility testing is the next step with successful implementation requiring senior health leadership support and involvement of co-design members as change agents. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.